The effects of leg cycling training on lactate threshold and maximal oxygen consumption measured during leg cycling and arm cranking exercise. - Saumure, Nancy E. (University of Ottawa (Canada), 1991)
The purpose of this study was to determine if the training effects on lactate threshold (LT) and maximal oxygen consumption (VO$\sb2$max) are specific to musculature involved in training or if there is evidence of a general training effect, such that adaptations are also found during exercise with untrained muscle groups. Seven moderately active male students participated in an eight week progressive endurance training program that involved leg cycling at specific intensities above and below the pre-training LT to give a total of 30 minutes of training above LT three times per week. All subjects were tested before and after training for LT and VO$\sb2$max while performing leg cycling and arm cranking exercises. VO$\sb2$max showed a significant increase during both leg cycling and arm cranking exercise following training. Conversely, increases in both absolute and relative LT were confined to leg cycling exercise only. It is suggested that peripheral adaptive responses of oxidative capacity within the trained muscles are primarily responsible for the specificity of the LT response, while cardiovascular adaptations were beneficial to VO$\sb2$max of both of the muscle groups tested. Furthermore, the significant improvement in relative LT during leg cycling and of VO$\sb2$max to both arm and leg exercise suggests that adaptive responses of LT and VO$\sb2$max to training are not governed by the same physiological processes. Therefore, it was concluded that, for the conditions of this experiment, the concept of specificity of training applies to LT but not to VO$\sb2$max when comparing exercise modalities which involve separate musculature.
Keywords: Biology, Animal Physiology.